Population trends in mitral valve surgery in Finland between 1997 and 2014: the finnish CVD register - Myllykangas ME; Aittokallio JM; Pietilä A; Salomaa VV; Gunn JM; Kiviniemi TO; Niiranen TJ (Taylor & Francis, 2025)
OBJECTIVES:
Contemporary, nationwide data on trends in mitral valve surgery are scarce. Our aim was to investigate changes in procedure rates, patient selection, and post-procedural prognosis of open-heart mitral valve surgery in Finland.
DESIGN:
We combined data from three nationwide administrative registers with compulsory reporting. We identified patients who had undergone first-ever open-heart mitral valve surgery between 1997 and 2014 and followed them for adverse events. We examined trends in mitral valve surgery over three six-year time periods (1997-2002, 2003-2008, and 2009-2014).
RESULTS:
3684 mitral valve procedures (mean age: 67.0 ± 10.9 years, 42.6% women) were performed in 1997-2014 in Finland. During this period, mitral valve repair operations became more common than replacements and we observed an increasing trend in the use of bioprosthetic valves. Between 1997-2002 and 2009-2014, the mean age of patients undergoing mitral valve surgery and the proportion of urgent surgeries increased (p < .001 for both). The proportion of women undergoing surgery decreased while the share of patients with hypertension (p = .023) or diabetes (p = .026) increased. The multivariable-adjusted risk of 28-day (hazard ratio, 0.55; 95% confidence interval, 0.37-0.83) and 6-year (hazard ratio, 0.80; 95% confidence interval, 0.67-0.97) post-operative mortality was lower in the last six-year period than in 1994-1998.
CONCLUSIONS:
Short- and long-term mortality of mitral valve surgery patients in Finland has decreased from 1997 to 2014 despite the patients being older and having more comorbidities. Understanding the changing characteristics and prognosis of these patients is important for the interpretation of previous and future cohort studies and trials.